Peningkatan Meningkatkan Hasil Belajar Peserta Didik Melalui Pembelajaran Berdiferensiasi di Kelas IV SD Negeri 8 Limboto Barat Kab. Gorontalo - Fadila Djou; Abdurahman R. Mala; Anugrah Lestari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning outcomes refer to the abilities that students possess after undergoing learning experiences, including their understanding and knowledge. This study examines the improvement of learning outcomes in Islamic Religious Education (PAI) by implementing differentiated instruction on the topic of Faith in the Messengers of Allah in Grade IV of SD Negeri 8 Limboto Barat, Gorontalo Regency. This research is a Classroom Action Research (CAR). Data collection techniques included observation, interviews, and documentation using research instruments such as teacher activity observation sheets, student activity observation sheets, tests, and student learning outcome sheets. The data analysis technique followed the procedures of classroom action research, employing both descriptive and quantitative analysis. The results of this study show that the implementation of differentiated instruction improved students' learning outcomes in the PAI subject on the topic of Faith in the Messengers of Allah. This improvement can be seen in the increase in teacher activity, which rose from 69% in Cycle I to 100% in Cycle II. Similarly, student learning activity increased from 56% in Cycle I to 83% in Cycle II. Student learning outcomes in PAI also improved significantly. In the pre-cycle phase, only 8 out of 20 students (40%) achieved mastery. This increased to 14 students (70%) in Cycle I with an average mastery score of 78.00, and further improved in Cycle II, with 19 students (95%) achieving mastery and an average score of 85.00.